Hot snare vs. cold snare polypectomy for endoscopic removal of 4 – 10 mm colorectal polyps during colonoscopy: a systematic review and meta-analysis of randomized controlled studies - Jegadeesan, Ramprasad; Aziz, Muhammad; Desai, Madhav; Sundararajan, Tharani; Gorrepati, Venkata Subhash; Chandrasekar, Viveksandeep Thogulva; Jayaraj, Mahendran; Singh, Pratiksha; Saeed, Ahmed; Rai, Tarun; Choudhary, Abhishek; Repici, Alessandro; Hassan, Cesare; Fuccio, Lorenzo; Sharma, Prateek (Endoscopy International Open, 2019)
Introduction In recent years, cold snare polypectomy (CSP) has increasingly been used over hot snare polypectomy (HSP) for the removal of colorectal polyps (4 – 10 mm in size). However, the optimal technique (CSP vs. HSP), in terms of complete polyp resection and complications, is uncertain. Our aim was to compare incomplete resection rate (IRR) of polyps and complications using CSP vs. HSP.Methods Randomized controlled studies (RCTs) comparing CSP and HSP for removal of 4 – 10 mm colorectal polyps were considered. Studies were included in the analysis if they obtained biopsy specimens from the resection margin to confirm the absence of residual tissue and reported complications. IRR and complication rate were the outcome measures. Pooled rates were reported as Odds Ratios (OR) or risk difference with 95 % Confidence Interval (CI).Results In total, three RCTs were included in the final analysis. A total of 1051 patients with 1485 polyps were randomized to either HSP group (n = 741 polyps) or CSP group (n = 744 polyps). The overall IRR did not differ between the two groups (HSP vs. CSP: 2.4 % vs. 4.7 %; OR 0.51, 95 %CI 0.13 – 1.99, P = 0.33, I2 = 73 %). The HSP group had a lower rate of overall complications compared to the CSP group (3.7 % vs. 6.6 %; OR 0.53, 95 % CI 0.3 – 0.94, P = 0.03, I2 = 0 %). Polyp retrieval rates were not different between the two groups (99 % vs. 98.1 %).Conclusion Our results suggest that HSP and CSP techniques can be effectively used for the complete removal of 4 – 10 mm colorectal polyps; however, HSP has a lower incidence of overall complications.